Very high density of Chinese hamster ovary cells in perfusion by alternating tangential flow or tangential flow filtration in WAVE bioreactor™—part II: Applications for antibody production and cryopreservation. (21st May 2013) - Clincke, Marie‐Françoise; Mölleryd, Carin; Samani, Puneeth K; Lindskog, Eva; Fäldt, Eric; Walsh, Kieron; Chotteau, Véronique
<x xml:space="preserve">Abstract</x> A high cell density perfusion process of monoclonal antibody (MAb) producing Chinese hamster ovary (CHO) cells was developed in disposable WAVE Bioreactor™ using external hollow fiber (HF) filter as cell separation device. Tangential flow filtration (TFF) and alternating tangential flow (ATF) systems were compared and process applications of high cell density perfusion were studied here: MAb production and cryopreservation. Operations by perfusion using microfiltration (MF) or ultrafiltration (UF) with ATF or TFF and by fed‐batch were compared. Cell densities higher than 108 cells/mL were obtained using UF TFF or UF ATF. The cells produced comparable amounts of MAb in perfusion by ATF or TFF, MF or UF. MAbs were partially retained by the MF using ATF or TFF but more severely using TFF. Consequently, MAbs were lost when cell broth was discarded from the bioreactor in the daily bleeds. The MAb cell‐specific productivity was comparable at cell densities up to 1.3 × 108 cells/mL in perfusion and was comparable or lower in fed‐batch. After 12 days, six times more MAbs were harvested using perfusion by ATF or TFF with MF or UF, compared to fed‐batch and 28× more in a 1‐month perfusion at 108 cells/mL density. Pumping at a recirculation rate up to 2.75 L/min did not damage the cells with the present TFF settings with HF short circuited. Cell cryopreservation at 0.5 × 108 and 108 cells/mL was performed using cells from a perfusion run at 108 cells/mL density. Cell resuscitation was very successful, showing that this system was a reliable process for cell bank manufacturing. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:768–777, 2013